KNOWLEDGE AND MOTIVATION OF WOMAN IN REPRODUCTIVE AGE GIVEN HEALTH EDUCATION ABOUT EARLY DETECTION OF CERVICAL CANCER - Arum Estiyani; Sigit Ambar W; Ima Syamrotul; Wulan Margiana (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Cancer is a serious threat to public health because the incidence and its death rates is inarpasing to increase every year. Cancer of the cervix is one of the malignancies or neoplasms that occur in the cervix, which is the lowest part of the uterus that protrudes into the peak hole intercourse (vaginal). In to control cervical cancer, the government is targeting at least 80% of women aged 30- 50 years old do early detection every 5 years. Early detection by using IVA (visual inspection with acetate acid) is not much known by the public One of the methods to expand the information about it is to provide health education wich can increase knowledge and motivation of woman in reproductive age to do for the early detection of cervical cancer. This study aimed to analyze the differences of knowledge and motivation woman in reproductive age before and after health education about cervical cancer early detection. Methode: The study design used pre-experimentalpre-post test one group design with the intervention of health education. The population was all woman in reproductive in Sidomukti Village District of Semarang District Bandungan as many as 875 people. The Samples were 27 respondents using proportional random sampling technique. Measuring instrument used questionnaires. The data analysis used Wilcoxontest. Results: The results showed thatthere caresignificantdifferences of knowledge and motivation of woman in reproductive age given before and after health education about early detection of cervical cancer in rural Sidomukti Bandungan district of Semarang district. which Wilcoxon test result showed pvalue = 0,000 < α (0,05). Conclusion: It is hoped than is more health education or disseminate information about early detection of cervical cancer with IVA (visual inspection with acetate acid) method. This can be done through the provision of information, such as counseling or providing information directly to the mother while visiting health facilities so that the incidence of cervical cancer can be lowered.